Google's Cybersecurity Framework (International Journal of Innovative Research in Engineering & Management, 2022)
Cybersecurity is a fundamental concept in  modern-day organizations. Firms are constantly exploring  security solutions to keep them secure from security  compromises that bear a great potential of disrupting their  daily operations. The cybersecurity landscape is highly  diverse and incorporates numerous elements that firms can  exploit to protect vital corporate systems, including networks  and sensitive resources such as data. Google is highly  conscious of cybersecurity and employs every measure to  protect its vital IT resources and systems from security  threats. Google’s cybersecurity landscape is significantly  mature and employs multiple plans that guarantee  infrastructural security, data asset management, and effective  access control. The firm’s security policies greatly prioritize  promoting employee security awareness as the firm  understands that workers form a fundamental component of  its entire cybersecurity plan. This paper explores Google’s  cybersecurity plan by focusing on cybersecurity security  awareness programs, company information exposure on  social networking sites, and the effects of not using  encryption on network or Internet traffic. The paper will  similarly recommend ways of minimizing information  exposure while developing an understanding between  password strengths and password managers in cybersecurity.
Keywords: Google; Cybersecurity; Application; Network; Encryption; Software; Internet